The Sound of the kiss, or, the story that must never be told : Piṅgaḷi Sūrana's Kaḷāpūrṇodayamu - Piṅgaḷi Sūrana; Narayana Rao, Velcheru, 1932-; Shulman, David Dean, 1949- (New York : Columbia University Press, 2002)
In this sixteenth-century masterpiece of Telugu literature, from the region now known as Andhra Pradesh, Suranna recounts the story of a young courtesan who falls in love with the most handsome man in the universe and overhears him speaking of a mysterious person whose story must never be told. Burning with curiosity and desire, she ventures to the god Krishna's palace, where much intrigue and adventure ensue. The Sound of the Kiss is considered by some to be the first novel written in South Asia, and the translation of this classic fills a gap in the literature of the East.</P.
The Baby Who TalksSarasvati Decodes Brahma's Story; Manistambha and Sumukhasatti Exchange Genders; A Lecture on Yoga; Svabhava and Madasaya at Srisailam; Chapter 6; Manikandhara Fights the Porcupine Demon; The Story of Alaghuvrata and His Sons; Satvadatma's Question; Madhuralalasa Comes of Age; Chapter 7; Kalapurna in Love; The Wedding of Kalapurna and Madhuralalasa; Abhinavakaumudi Becomes Jealous; Chapter 8; Kalapurna Conquers the World; Homecoming; The Story of the Necklace; Invitation to a Second Reading; Guide to Pronunctiation and List of Characters; Index of Names and Technical Terms.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Love stories, South Asian -- 16th century -- Translations into English; South Asia -- 16th century -- Translations into English; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; LITERARY CRITICISM -- Asian -- Indic; South Asia; 1500-1599; Translations